Laboratory statistics methods in chemistry and health sciences - Kallner, Anders (Elsevier, 2018)
"Presents strategies for comparing and evaluating numerical laboratory data. The text deals with the data and problems that laboratory scientists and students in analytical chemistry, clinical chemistry, epidemiology, and clinical research face on a daily basis. The book takes the mystery out of statistics and provides simple, hands-on instructions in the format of everyday formulas, spreadsheet shortcuts and functions, and many simple worked examples. This thoroughly revised second edition includes several new sections, more examples, and all formulas in Excel code."